Evaluation of Vacuum Assisted Wound Closure and Conventional Wound Closure In Contaminated Major Surgical Wound (IAHS Medical Journal, 2023)
Background: Surgical Site Infections (SSI) increase costs, hospital stay, morbidity, and mortality. Vacuum-Assisted Closures (VAC) system has been gaining popularity recently in managing wounds to reduce SSI. But the current guidelines do not recommend its routine use for surgical wounds. This study aimed to compare the effectiveness and safety of VAC with conventional wound closure techniques for preventing SSIs in the major contaminated surgical wound.Methods and materials: Sixty patients with a contaminated surgical wound from the Department of Surgery and Department of Casualty of Chittagong Medical College Hospital were randomized in a 1:1 ratio to receive either VAC (Using Romovac device) or conventional wound closure. The primary endpoint was the rate of uncomplicated wound healing, defined as a Southampton wound score of